Atomistic investigation on the wetting behavior and interfacial joining of polymer-metal interface - Zhou, Mingyong; Fu, Liang; Jiang, Fengze; Jiang, Bingyan; Drummer, Dietmar (Polymers, 2020)
Polymer-metal hybrid structures can reduce the weight of components while ensuring the structural strength, which in turn save cost and subsequently fuel consumption. The interface strength of polymer-metal hybrid structure is mainly determined by the synergistic effects of interfacial interaction and mechanical interlocking. In this study, the wetting behavior of polypropylene (PP) melt on metal surface was studied by molecular dynamics simulation. Atomistic models with smooth surface and nano-column arrays on Al substrate were constructed. Influences of melt temperature, surface roughness and metal material on the wetting behavior and interfacial joining were analyzed. Afterwards the separation process of injection-molded PP-metal hybrid structure was simulated to analyze joining strength. Results show that the initially sphere-like PP model gradually collapses in the wetting simulation. With a higher temperature, it is easier for molecule chains to spread along the surface. For substrate with rough surface, high density is observed at the bottom or on the upper surface of the column. The contact state is transitioning fromWenzel state to Cassie-Baxter state with the decrease of void fraction. The inner force of injection-molded PP-Fe hybrid structure during the separation process is obviously higher, demonstrating a greater joining strength.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Injection-molded direct joining; Interfacial interaction; Molecular dynamics simulation; Polymer-metal hybrid; Wetting behavior